Toward a Better Understanding of Language Learning Motivation in a Study Abroad Context: An Investigation Among Chinese English as a Foreign Language Learners - Yue, Zhen; Zhao, Kai; Meng, Yaru; Qian, Xi; Wu, Lin (Frontiers in Psychology, 2022)
Motivation has been recognized as a vital component in successfully learning a second or foreign language. However, research on language learners’ motivation in a study abroad context requires more attention in an era in which international mobility is becoming a new normal. This study investigated 217 Chinese overseas university students’ L2 motivation during their one-year postgraduate study in the U.K. by examining a range of motivational variables in relation to their motivated English language learning behaviours. Integrating results from both questionnaires and interviews from nine participating students, the study revealed that international posture showed the strongest positive power, followed by the ideal L2 self, in explaining the learners’ willingness to communicate, frequency of communication, and intended learning effort. Additionally, instrumentality and parental encouragement exerted prominent promotional influence in shaping their intended learning effort. However, the ought-to L2 self displayed a significant negative impact on their L2 learning in this study abroad context, and the role of attitudes toward L2 speakers/community and culture was not evident in this case. The findings shed light on a more comprehensive understanding of L2 motivation in a study abroad context, and offer insightful implications for EFL education in cultivating language learners’ motivation to prepare for study abroad.